Farmers’ Willingness To Pay For Livestock Insurance Programs In Kulon Progo District - Tri Kurniaty; Masyhuri Masyhuri; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2021)
Livestock Insurance is one of the insurance products supported by the government with PT Jasindo as the organizer. Livestock insurance will provide the potential for cattle ranchers who can get risk threats such as cattle deaths due to illness, accidents, losses caused by theft, and deaths due to breeding. This study aims to determine the value of the willingness of farmers to pay the insurance and the factors that affect the willingness of farmers to pay insurance. This research was conducted from February to March 2020 in the Kulon Progo district. Location determination is done by purposive sampling based on data from the farmer following the insurance program. Primary data obtained from 53 farmers with the help of a questionnaire and analyzed by the method of contingency value (CVM) and multiple linear regression. The research shows the average value of willingness to pay insurance is IDR45,660 per head per year above the value of the insurance premium assessment. Factors that significantly influence a Farmer's Willingness to Pay (WTP) for the Insurance program are the variable number of family dependants and income, while the age, duration of raising, and education have no significant effect. Based on the value of the EWTP obtained, which is very low, the expectation of farmers is not to demand too low a price.